Voltammetric Investigation of Hydrothermal Iron Speciation - Kleint, Charlotte; Hawkes, Jeffrey A.; Sander, Sylvia G.; Koschinsky, Andrea (Frontiers in Marine Science, 2016)
Hydrothermal vent fluids are highly enriched in iron (Fe) compared to ambient seawater, and organic ligands may play a role in facilitating the transport of some hydrothermal Fe into the open ocean. This is important since Fe is a limiting micronutrient for primary production in large parts of the world`s surface ocean. We have investigated the concentration and speciation of Fe in several vent fluid and plume samples from the Nifonea vent field, Coriolis Troughs, New Hebrides Island Arc, South Pacific Ocean using competitive ligand exchange - adsorptive cathodic stripping voltammetry (CLE - AdCSV) with salicylaldoxime (SA) as the artificial ligand. Our results for total dissolved Fe (dFe) in the buoyant hydrothermal plume samples showed concentrations up to 3.86 µM dFe with only a small fraction between 1.1% and 11.8% being chemically labile. Iron binding ligand concentrations ([L]) were found in µM level with strong conditional stability constants up to log K[L],Fe3+ of 22.9. Within the non-buoyant hydrothermal plume above the Nifonea vent field, up to 84.7% of the available Fe is chemically labile and [L] concentrations up to 97 nM were measured. [L] was consistently in excess of Felab, indicating that all available Fe is being complexed, which in combination with high Felab values in the non-buoyant plume, signifies that a high fraction of hydrothermal dFe is potentially being transported away from the plume into the surrounding waters, contributing to the global oceanic Fe budget.